Guidelines for retracting articles - Committe on Publication Ethics, COPE (Boletim Técnico do PPEC, 2019)
Retraction is a mechanism for correcting the literature and alerting readers to articles that contain such seriously flawed or erroneous content or data that their findings and conclusions cannot be relied upon. Unreliable content or data may result from honest error, naïve mistakes, or research misconduct. The main purpose of retraction is to correct the literature and ensure its integrity rather than to punish the authors. Retractions may be used to alert readers to cases of redundant publication, plagiarism, peer review manipulation, reuse of material or data without authorisation, copyright infringement or some other legal issue (eg, libel, privacy, illegality), unethical research, and/or a failure to disclose a majorcompeting interest that would have unduly influenced interpretations or recommendations.